Psychology of sport injury - Brewer, Britton W.; Redmond, Charles J. 1946- (Champaign, IL Human Kinetics, 2017)
From a gymnast hiding ankle pain so she can compete to a basketball player who withdraws from friends after a season-ending injury, it can be argued that every sport injury affects or is affected in some way by psychological factors. Given the widespread importance of psychological issues in sport injury, it is important for those working with athletes--injured or not--to be aware of the latest developments on the subject. Written by a sport psychology consultant and an athletic trainer, Psychology of Sport Injury provides a thorough explanation of the elements and effects of sport injuries along with up-to-date research and insights for practical application. The authors offer a contemporary approach to preventing, treating, rehabilitating, and communicating professionally about sport injuries that takes into account physical, psychological, and social factors. Psychology of Sport Injury presents sport injury within a broader context of public health and offers insights into the many areas in which psychology may affect athletes, such as risk culture, the many facets of pain, athlete adherence to rehab regimens, the relationship between psychological factors and clinical outcomes, collaboration, and referrals for additional support. The book explores the relevant biological, psychological, and social factors that affect given circumstances. The text consists of four parts: Understanding and Preventing Sport Injuries, Consequences of Sport Injury, Rehabilitation of Sport Injury, and Communication in Sport Injury Management. Psychology of Sport Injury includes evidence-based examples and demonstrates real-world applications that sport health care professionals often face with athletes. Additional pedagogical features include the following: Focus on Research boxes provide the what and why of the latest research to complement the applied approach of the text; Focus on Application boxes highlight practical examples to illustrate the material and maintain student engagement; Psychosocial content aligned with the latest educational competencies of the National Athletic Trainers' Association (NATA) helps students prepare for athletic training examinations and supports professional development for practitioners; A prevention-to-rehabilitation approach gives a framework for understanding sport injury, including precursors to injury, pain as a complex phenomenon, adherence to rehabilitation, and communication and management of injuries with other health care professionals as well as the athlete; A set of chapter quizzes and a presentation package aid instructors in testing student comprehension and preparing lectures. Psychology of Sport Injury is an educational tool, reference text, and springboard to new ideas for research and practice in any line of work exposed to sport injury. Observing and committing to athletes, especially during times of physical trauma and emotional distress (which are often not separate times), are critical skills for athletic trainers, physical therapists, sport psychologists, coaches, and others who work with athletes on a regular basis.
Part I. Understanding and Preventing Sport Injuries -- Chapter 1. Biopsychosocial Foundations of Sport Injury ; A Biopsychosocial Perspective on Sport Injury ; Biological Foundations of Sport Injury ; Psychological Foundations of Sport Injury ; Social Foundations of Sport Injury ; Biopsychosocial Analysis ; Summary -- Chapter 2. Antecedents of Sport Injury ; Models of Sport Injury Occurrence ; Psychosocial Predictors of Sport Injury ; Mechanisms of Psychosocial Influence on Sport Injury Occurrence ; Biopsychosocial Analysis ; Summary -- Chapter 3. Sport Injury Prevention ; Types of Prevention ; Models of Sport Injury Prevention ; Sport Injury Prevention Content Categories ; Biopsychosocial Analysis ; Summary -- Part II. Consequences of Sport Injury -- Chapter 4. Psychological Responses to Sport Injury ; Models of Psychological Response to Sport Injury ; Psychological Consequences of Sport Injury ; Biopsychosocial Analysis ; Summary -- Chapter 5. Pain, Sport, and Injury ; Definitions of Pain ; Types of Pain ; Dimensions of Pain ; Measurement of Pain ; Models and Theories of Pain ; Factors Associated with Pain in Sport ; Interpreting and Acting on Sport-Related Pain ; Biopsychosocial Analysis ; Summary -- Part III. Rehabilitation of Sport Injury -- Chapter 6. Adherence to Sport Injury Prevention and Rehabilitation Programs ; Adherence to Sport Injury Prevention Programs ; Adherence to Sport Injury Prevention Programs ; Consequences of Adherence to Sport Injury Prevention and Rehabilitation Programs ; Biopsychosocial Analysis ; Summary -- Chapter 7. Psychological Factors in Sport Injury Rehabilitation ; Sport Injury Rehabilitation Outcomes ; Charting a Course from Psychological Factors to Sport Injury Rehabilitation Outcomes ; Psychological Readiness to Return to Sport ; Biopsychosocial Analysis ; Summary -- Chapter 8. Psychological Interventions in Sports Health Care ; Psychological Interventions in Sports Health Care ; Biopsychosocial Analysis ; Summary -- Part IV. Communication in Sport Injury Management -- Chapter 9. Communicating with Patients ; Context of Patient-Practitioner Communication in Sports Health Care ; Models of the Patient-Practitioner Relationship in Sports Health Care ; Congruence of Patient-Practitioner Perceptions in Sports Health Care ; Factors Affecting Patient-Practitioner Communication in Sports Health Care ; Biopsychosocial Analysis ; Summary -- Chapter 10. Referring Athletes for Psychological Services ; Definition of and Rationale for Referral of Athletes for Psychological Services ; Socioclinical Context of Referral of Athletes for Psychological Services ; Reasons for Referral ; Referral Process ; Biopsychosocial Analysis ; Summary.
Includes bibliographical references
Also available in print format
Keywords: Athletes -- Psychology; Sports -- Psychological aspects; Sports -- Sociological aspects; Sports injuries -- Psychology